Determinant of Lecturers Work Satisfaction and Implication on Lecturers Performance at Maritime Higher Education in DKI Jakarta - Gunawan, April; Barsa, Larsen; Tua, Hotman (International Review of Management and Marketing, 2018)
This study aimed to examine the determinants of lecturers job satisfaction and their implication on the lecturers performance in conducting research at Maritime Higher Education in DKI Jakarta. The sample data is 286 people and the retrieval for instrument test is 30 people so the research population is 316 people. To prove the hypothesis of this study using data collected by statistics, both descriptive and inferential, ie Structural Equation Modeling (SEM), consisting of sub-structures: perceived organizational support, work-life balance, and career development as exogenous variables and job satisfaction and performance as an endogenous variable. The main structure consists of perceived organizational support, work-life balance and career development as exogenous variables and job satisfaction as intervening variables and performance as endogenous variables. Through SEM analysis can be taken policy and priority related to improving the lecturers performance at Maritime Higher Education in DKI Jakarta. The results showed: (1) Partially influences positive and significant perceived organizational support to the job satisfaction (2) Partially, there are positive and significant impact of work life balance on job satisfaction. (3) Partially there is a positive and significant influence of career development on job satisfaction. (4) Simultaneously there is positive and significant influence perceived organizational support, work life balance and career development together to the job satisfaction. (5) Partially there is positive and significant influence perceived organizational support to lecturers performance (6) Partially, there are positive and significant impact of work life balance on lecturers performance (7) Partially there is a positive and significant influence of career developers on the lecturers performance (8) Partially influences positive and significant satisfaction on the lecturers performance. (9) Simultaneously there are positive and significant influence perceived organizational support, work life balance, career development and job satisfaction together to the lecturers performance at Maritime Higher Education in DKI Jakarta Keywords: Perceived Organizational Support, Work Life Balance, Career Development, Job Satisfaction, Lecturers Performance JEL Classifications: M12, M54, N75